Qingchang Wenzhong Decoction Prevents the Occurrence of Intestinal Tumors by Regulating Intestinal Microbiota and Gasdermin E - Ren, Lingli; Zhang, Zhengwei; Zhao, Wenjing; Zhao, Bing; Chen, Xi; Wang, Yongxiang; Chen, Zhong; Ye, Juan; Yang, Yang; Cao, Peng (Frontiers in Physiology, 2022)
Background: Intestinal tumors are the third most common malignant tumors worldwide, accounting for approximately 10% of all new cancer cases worldwide. Cancer prevention is a promising way to limit the intestinal tumor incidence rate; however, challenges remain. Qingchang Wenzhong decoction (QCWZD) can clinically treat mild to moderate ulcerative colitis symptoms. Moreover, the mechanism by which it prevents intestinal tumors has not been clarified. In this study, we explored the mechanism by which QCWZD prevents the occurrence of intestinal tumors. Methods: To study the preventive mechanism of QCWZD on intestinal tumors, we used two model mice with azoxymethane/dextran sodium sulfate (AOM/DSS)- and Apcmin/+-induced intestinal tumor formation. The two models exhibited colitis-associated cancer and familial adenomatous polyposis, respectively. Colon and small intestine tissues were collected and analyzed based on histopathology and immunohistochemistry analyses. Fecal samples were collected, and 16S rRNA sequencing was used to analyze the correlation between intestinal microbiota and the prevention of intestinal tumors. Results: In the AOM/DSS mice, the QCWZD reduced the number and size of tumors, as well as tumor load. Similarly, in the Apcmin/+ mice, QCWZD can also reduce the number of tumors and the tumor load. The results of 16S rRNA sequencing confirmed that QCWZD altered the composition of intestinal microbiota in mice, a phenomenon that may prevent the occurrence of intestinal tumors by aiding the increase in the abundance of beneficial bacteria, such as Ralstonia and Butyricicoccus, and reducing that of pathogenic bacteria, such as Desulfobacterota and Bacteroides, in the intestine. Further, immunohistochemistry reveald that QCWZD can improve the expression of intestinal barrier-related proteins and inhibit pyroptosis-related proteins. Conclusions: QCWZD has the potential to prevent the occurrence of intestinal tumors. The anti-tumor activity may be achieved by regulating the intestinal microbiota, improving the function of the intestinal barrier, and inhibiting GSDME mediated pyroptosis.